Privatisation of Electric Power Sector in Pakistan: Some Important Issues (The Pakistan Development Review, 1999)
The electric power sector in Pakistan is growing faster (II percent) than the average growth rate of other developing countries (10 percent). However, the demand in Pakistan is growing even faster than the supply and therefore power shortage has become a serious problem. The problem is compounded by inefficiency of electric power sector. Moreover there is underpril:ing. subsidising, overstaffing and inadequate maintenance. Like many other developing countries, Pakistan has also opted for "privatisation" in the form of transfer of ownership as the first best solution. However, a wide range of literature argues that such type of privatisation in the case of electric power may not lead to miracles. The present a11icle attempts to analyse the past inefficiency of the electric power sector in Pakistan and performs a diagnostic analysis to identify sources and causes of inefficiencies. This analysis does not necessarily support a strict privatisation based reform. The article further discusses the salient feature of privatisation of electric power sector in Pakistan' and some important issu,es related to its feasibility. It is noted that the privatisation of electric power sector in Pakistan, as pursued now, may not resolve the problems of this sector. It may ease short-run financial constraints but it may also create a number of long-term problems such as inappropriate planning, greater energy dependence and insecurity. It is also noted that current problems stem primarily from institutional and organisational constraints faced by public sector power enterprises. The key issue may not be a choice between public or private ownership but to determine an appropriate reform package based on either public/private or a mixed ownership structure, that encourages greater private involvement and functions well in the specific environment of Pakistan.